Estimating variability in point load resistance of fibre reinforced shotcrete linings. (July 2022) - Bernard, E.S.; Coleman, R.
Highlights: Variability in material performance was obtained for FRS linings. A model was developed to estimate variability in load resistance of FRS linings. Both flexural and punching shear failure was considered. Calculated variability in load resistance was close to measured variability in load resistance obtained from full scale tests. Abstract: In the design of fibre reinforced shotcrete linings, the focus of attention is usually fixed on determining the maximum load capacity to satisfy ultimate limit state requirements. Less attention is focused on determining the variability in capacity, both in service and at ultimate load, but this variability is relevant to identification of a suitable partial safety factor for lining load capacity. To help address this deficit, a series of analyses have been undertaken to assess the likely magnitude of variation in the flexural and punching shear resistance of fibre reinforced shotcrete linings. The analyses have been based on an assessment of the propagation of variances using analytical and semi-empirical models of flexural and punching resistance. When compared to observed variability in full-scale tests of lining capacity, the analyses produce acceptable estimates of the measured Coefficient of Variation in lining load resistance.